Motivation, Welfare, and Work Spirit as Drivers of Employee Performance - Sopiyan, Pipih; Sudirno, Dadang; Masduki; Azis, Fajar Muhamad (Finance and Business Management Journal, 2025)
Employee performance at PT. Sindangkasih Multi Usaha (Perseroda) Majalengka Regency shows an interesting phenomenon that deserves attention, where there are indications of significant variations between company expectations and the realization of individual and team achievements. Initial observations show that although the company has a clear organizational structure and targets, implementation in the field is sometimes not aligned, marked by fluctuations in target achievement, productivity levels, and compliance with standard operating procedures. This phenomenon is very relevant to further research because employee performance is the backbone of the success of regional companies in achieving business goals, providing optimal public services, and contributing to the economic development of Majalengka Regency. This study aims to determine the effect of motivation, work welfare and enthusiasm on employee performance. The research method used is a survey method with a descriptive verification approach. The population in this study were 83 employees of PT. Sindangkasih Multi Usaha (Perseroda) Majalengka Regency. With a saturated sampling technique, the entire population was sampled. The analysis technique used multiple linear regression analysis, coefficient of determination analysis, which first conducted a classical assumption test, then conducted a hypothesis test. The results of the study indicate that motivation, welfare, and work enthusiasm partially have a positive and significant effect on employee performance at PT. Sindangkasih Multi Usaha (Perseroda) Majalengka Regency.